Fracture at the Modular Junction of a Cementless Revision Hip System: A Case Report. Issue 2 (April 2016) - Duncan, Stephen T.; Hayes, Christopher B.; Nunley, Ryan M.
Abstract : Case: Multiple cases of modular femoral component failure involving fatigue at the modular stem junction have been reported following revision total hip arthroplasty. In the present report, we describe what we believe to be the first case of catastrophic failure involving the Biomet Arcos revision system. The failure involved a young patient with an elevated body mass index and proximal bone deficiency. Conclusion: The possibility of this failure mechanism must be weighed against the potential advantages of modular cementless stems when planning for complex hip arthroplasty, especially in the young, active patient.